Isu dan Peermasalahan Peserta Didik: Tantangan dan Solusi dalam Pendidikan Indonesia - Nabila Septiana; Sustia Ningsih; Bilal Bilal; Sani Safitri; Syarifuddin Syarifuddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Education in Indonesia is facing a number of challenges and issues related to students, reflecting the complexity of the national education system in social, economic, and cultural contexts. Various elements such as inequality in access to education, variations in the quality of facilities, family economic constraints, and socio-cultural differences affect the learning process and growth of students. In addition, internal problems such as low enthusiasm for learning, lack of literacy and numeracy skills, and violence in schools further add to the complexity of education. The purpose of this article is to identify the main problems faced by students in Indonesia, analyze their causes, and develop relevant alternative solutions to improve the quality of education. By utilizing a literature analysis approach and empirical data study, this article highlights the importance of cooperation between all parties, improving teacher capacity, optimizing the role of parents, and implementing inclusive and adaptive education policies. Numerous student-related problems plague Indonesian education, including unequal access to education, insufficient motivation for learning, and social and psychological problems that affect academic achievement. Numerous factors, such as differences in the caliber of teachers, a lack of educational resources, and socioeconomic background, contribute to this situation. All-encompassing solutions are needed for these problems, including improving the curriculum, increasing teacher competency, and implementing a more flexible and inclusive teaching approach that considers the needs of the students. This article discusses the primary issues faced by Indonesian students and offers practical solutions in order to create a more equitable, effective, and sustainable educational system.